The Role of Work Motivation in Mediating the Effect of Workload and Competence on the Performance of Functional Planning Officers in Klungkung Regency - Krusita, Ni Wayan Yulia; Sara, I Made; Sitiari, Ni Wayan; Wibawa, I Gede Agus (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the role of work motivation in mediating the effect of workload and competence on the performance of Functional Planning Officers in Klungkung Regency. The research is motivated by the gap between administrative performance assessments and the substantive quality of performance, high and complex workloads, limited technical competence, and suboptimal work motivation. This study employed a quantitative survey-based approach involving the entire population of Functional Planning Officers in Klungkung Regency, totaling 53 employees. The data were analyzed using the Partial Least Squares (PLS) method. The results indicate that workload has a positive and significant effect on employee performance, but a negative and significant effect on work motivation. Competence has a positive and significant effect on both work motivation and employee performance. Work motivation also has a positive and significant effect on employee performance and acts as a partial mediating variable in the relationship between workload and competence on employee performance. This study recommends optimizing workload management, improving employee competence through continuous technical training, strengthening work motivation through proportional and fair task assignments, and intensifying performance supervision as efforts to sustainably enhance performance quality.